"manishkumarphysics.in"
1
Trigonometric Equation
Tri gonometric Equation :
An equation involving one or more trigonometric ratios of an unknown angle is called a trigonometric
equation.
Solution of Trigonometric Equation :
A solution of trigonometric equation is the value of the unknown angle that satisfies the equation.
e.g. if sinu =
2
1
u =
4
t
,
4
3t
,
4
9t
,
4
11t
, ...........
Thus, the trigonometric equation may have infinite number of solutions (because of their periodic nature) and
can be classified as :
(i) Principal solution (ii) General solution.
Principal solutions :
The solutions of a trigonometric equation which lie in the interval [0, 2t) are called Principal solutions.
e.g. Find the Principal solutions of the equation sinx =
2
1
.
Solution :
sinx =
2
1
there exists two values
i.e.
6
t
and
6
5t
which lie in [0, 2t) and whose sine is
2
1
Principal solutions of the equation sinx =
2
1
are
6
t
,
6
5t
General Solution :
The expression involving an integer 'n' which gives all solutions of a trigonometric equation is called
General solution.
General solution of some standard trigonometric equations are given below.
General Solution of Some Standard Trigonometric Equations :
(i) If sin u = sin o u = n t + (1)
n
o where o e
(
t t
2
,
2
, n e I.
(ii) If cos u = cos o u = 2 nt o where o e [0, t], n e I.
(iii) If tan u = tan o u = n t + o where o e 
.

\
 t t
2
,
2
, n e I.
(iv) If sin u = sin o u = n t o, n e I.
(v) If cos u = cos o u = n t o, n e I.
(vi) If tan u = tan o u = n t o, n e I. [Note: o is called the principal angle ]
MATHS
"manishkumarphysics.in"
2
Some Important deductions :
(i) sinu = 0 u = nt, n e I
(ii) sinu = 1 u = (4n + 1)
2
t
,n e I
(iii) sinu = 1 u = (4n 1)
2
t
, n e I
(iv) cosu = 0 u = (2n + 1)
2
t
,n e I
(v) cosu = 1 u = 2nt, n e I
(vi) cosu = 1 u = (2n + 1)t, n e I
(vii) tanu = 0 u = nt, n e I
Example # 1 : Solve sin u =
2
3
.
Solution : sin u =
2
3
sinu = sin
3
t
u = nt + ( 1)
n
3
t
, n e I
Example # 2 : Solve : sec 2u =
3
2
Solution : sec 2u =
3
2
cos2u =
2
3
cos2u = cos
6
5t
2u = 2nt
6
5t
, n e I
u = nt
12
5t
, n e I
Example # 3 : Solve tanu = 2
Solution : tanu = 2 ............(i)
Let 2 = tano tanu = tano
u = nt + o, where o = tan
1
(2), n e I
Self Practice Problems :
(1) Solve cotu = 1
(2) Solve cos3u =
2
1
MATHS
"manishkumarphysics.in"
3
Answers : (1) u = nt
4
t
, n e I (2)
3
n 2 t
9
2t
, n e I
Example # 4 : Solve cos
2
u =
2
1
Solution : cos
2
u =
2
1
cos
2
u =
2
2
1


.

\

cos
2
u = cos
2
4
t
u = nt
4
t
, n e I
Example # 5 : Solve 4 tan
2
u = 3sec
2
u
Solution : 4 tan
2
u = 3sec
2
u .............(i)
For equation (i) to be defined u = (2n + 1)
2
t
, n e I
equation (i) can be written as:
u
u
2
2
cos
sin 4
=
u
2
cos
3
u = (2n + 1)
2
t
, n e I
cos
2
u = 0
4 sin
2
u = 3 sin
2
u =
2
2
3


.

\

sin
2
u = sin
2
3
t
u = nt
3
t
, n e I
Self Practice Problems :
(3) Solve 7cos
2
u + 3 sin
2
u = 4.
(4) Solve 2 sin
2
x + sin
2
2x = 2
Answers : (3) nt
3
t
, n e I (4) (2n + 1)
2
t
, n e I or nt
4
t
, n e I
Types of Trigonometric Equations :
Type 1
Trigonometric equations which can be solved by use of factorization.
Example # 6 : Solve (2sinx cosx) (1 + cosx) = sin
2
x.
Solution : (2sinx cosx) (1 + cosx) = sin
2
x
(2sinx cosx) (1 + cosx) sin
2
x = 0
(2sinx cosx) (1 + cosx) (1 cosx) (1 + cosx) = 0
(1 + cosx) (2sinx 1) = 0
1 + cosx = 0 or 2sinx 1 = 0
MATHS
"manishkumarphysics.in"
4
cosx = 1 or sinx =
2
1
x = (2n + 1)t, n e I or sin x = sin
6
t
x = nt + ( 1)
n
6
t
, n e I
Solution of given equation is
(2n + 1)t, n e I or nt + (1)
n
6
t
, n e I
Self Practice Problems :
(5) Solve cos
3
x + cos
2
x 4cos
2
2
x
= 0
(6) Solve cot
2
u + 3cosecu + 3 = 0
Answers : (5) (2n + 1)t, n e I
(6) 2nt
2
t
, n e I or nt + (1)
n + 1
6
t
, n e I
Type  2
Trigonometric equations which can be solved by reducing them in quadratic equations.
Example # 7 : Solve 2 cos
2
x + 4cosx = 3sin
2
x
Solution : 2cos
2
x + 4cosx 3sin
2
x = 0
2cos
2
x + 4cosx 3(1 cos
2
x) = 0
5cos
2
x + 4cosx 3 = 0


.

\

+
5
19 2
x cos


.

\

5
19 2
x cos
= 0 ........(ii)
cosx e [ 1, 1] x e R
cosx =
5
19 2
equation (ii) will be true if cosx =
5
19 2 +
cosx = coso, where coso =
5
19 2 +
x = 2nt o where o = cos
1


.

\

+
5
19 2
, n e I
Self Practice Problems :
(7) Solve cos2u ( 2 + 1)


.

\

u
2
1
cos = 0
(8) Solve 4cosu 3secu = tanu
MATHS
"manishkumarphysics.in"
5
Answers : (7) 2nt
3
t
, n e I or 2nt
4
t
, n e I
(8) nt + ( 1)
n
o where o = sin
1


.

\

8
17 1
, n e I
or nt + (1)
n
 where  = sin
1


.

\

+
8
17 1
, n e I
Type  3
Trigonometric equations which can be solved by transforming a sum or difference of trigonometric
ratios into their product.
Example # 8 : Solve cos3x + sin2x sin4x = 0
Solution : cos3x + sin2x sin4x = 0 cos3x + 2cos3x.sin( x) = 0
cos3x 2cos3x.sinx = 0 cos3x (1 2sinx) = 0
cos3x = 0 or 1 2sinx = 0
3x = (2n + 1)
2
t
, n e I or sinx =
2
1
x = (2n + 1)
6
t
, n e I or x = nt + (1)
n
6
t
, n e I
solution of given equation is
(2n + 1)
6
t
, n e I or nt + (1)
n
6
t
, n e I
Self Practice Problems :
(9) Solve sin7u = sin3u + sinu
(10) Solve 5sinx + 6sin2x +5sin3x + sin4x = 0
(11) Solve cosu sin3u = cos2u
Answers : (9)
3
nt
, n e I or
2
nt
12
t
, n e I
(10)
2
nt
, n e I or 2nt
3
2t
, n e I
(11)
3
n 2 t
, n e I or 2nt
2
t
, n e I or nt +
4
t
, n e I
Type  4
Trigonometric equations which can be solved by transforming a product of trigonometric ratios into their
sum or difference.
Example # 9 : Solve sin5x.cos3x = sin6x.cos2x
Solution : sin5x.cos3x = sin6x.cos2x 2sin5x.cos3x = 2sin6x.cos2x
sin8x + sin2x = sin8x + sin4x sin4x sin2x = 0
MATHS
"manishkumarphysics.in"
6
2sin2x.cos2x sin2x = 0 sin2x (2cos2x 1) = 0
sin2x = 0 or 2cos2x 1 = 0
2x = nt, n e I or cos2x =
2
1
x =
2
nt
, n e I or 2x = 2nt
3
t
, n e I
x = nt
6
t
, n e I
Solution of given equation is
2
nt
, n e I or nt
6
t
, n e I
Type  5
Trigonometric Equations of the form a sinx + b cosx = c, where a, b, c e R, can be solved by dividing
both sides of the equation by
2 2
b a + .
Example #10 : Solve sinx + cosx = 2
Solution : sinx + cosx = 2 ..........(i)
Here a = 1, b = 1.
divide both sides of equation (i) by 2 , we get
sinx .
2
1
+ cosx.
2
1
= 1
sinx.sin
4
t
+ cosx.cos
4
t
= 1 cos 
.

\
 t
4
x
= 1
x
4
t
= 2nt, n e I x = 2nt +
4
t
, n e I
Solution of given equation is 2nt +
4
t
, n e I
Note : Trigonometric equation of the form a sinx + b cosx = c can also be solved by changing sinx and cosx
into their corresponding tangent of half the angle.
Example#11: Solve 3cosx + 4sinx = 5
Solution : 3cosx + 4sinx = 5 .........(i)
cosx =
2
x
tan 1
2
x
tan 1
2
2
+
& sinx =
2
x
tan 1
2
x
tan 2
2
+
equation (i) becomes
3




.

\

+
2
x
tan 1
2
x
tan 1
2
2
+ 4




.

\

+
2
x
tan 1
2
x
tan 2
2
= 5 ........(ii)
Let tan
2
x
= t
MATHS
"manishkumarphysics.in"
7
equation (ii) becomes 3


.

\

+
2
2
t 1
t 1
+ 4 
.

\

+
2
t 1
t 2
= 5
4t
2
4t + 1 = 0 (2t 1)
2
= 0
t =
2
1
t = tan
2
x
tan
2
x
=
2
1
tan
2
x
= tano, where tano =
2
1
2
x
= nt + o x = 2nt + 2o where o = tan
1

.

\

2
1
, n e I
Self Practice Problems :
(12) Solve 3 cosx + sinx = 2
(13) Solve sinx + tan
2
x
= 0
Answers : (12) 2nt +
6
t
, n e I (13) x = 2nt, n e I
Type  6
Trigonometric equations of the form P(sinx cosx, sinx cosx) = 0, where p(y, z) is a polynomial, can
be solved by using the substitution sinx cosx = t.
Example #12: Solve sinx + cosx = 1 + sinx.cosx
Solution : sinx + cosx = 1 + sinx.cosx ........(i)
Let sinx + cosx = t
sin
2
x + cos
2
x + 2 sinx.cosx = t
2
sinx.cosx =
2
1 t
2
in (i), we get t = 1 +
2
1 t
2
t
2
2t + 1 = 0
t = 1 t = sinx + cosx
sinx + cosx = 1 .........(ii)
divide both sides of equation (ii) by 2 , we get
sinx.
2
1
+ cosx.
2
1
=
2
1
cos 
.

\
 t
4
x = cos
4
t
x
4
t
= 2nt
4
t
(i) if we take positive sign, we get x = 2nt +
2
t
, n e I
(ii) if we take negative sign, we get
x = 2nt, n e I
MATHS
"manishkumarphysics.in"
8
Self Practice Problems:
(14) Solve sin2x + 5sinx + 1 + 5cosx = 0
(15) Solve 3cosx + 3sinx + sin3x cos3x = 0
(16) Solve (1 sin2x) (cosx sinx) = 1 2sin
2
x.
Answers : (14) nt
4
t
, n e I (15) nt
4
t
, n e I
(16) 2nt +
2
t
, n e I or 2nt, n e I or nt +
4
t
, n e I
Type  7
Trigonometric equations which can be solved by the use of boundness of the trigonometric ratios
sinx and cosx.
Example #13 : Solve sinx 
.

\

x sin 2
4
x
cos + x cos x cos 2
4
x
sin 1 
.

\

+ = 0
Solution : sinx 
.

\

x sin 2
4
x
cos +
x cos x cos 2
4
x
sin 1 
.

\

+
= 0 .......(i)
sinx.cos
4
x
2sin
2
x + cosx + sin
4
x
.cosx 2cos
2
x = 0

.

\

+ x cos .
4
x
sin
4
x
cos . x sin
2 (sin
2
x + cos
2
x) + cosx = 0
sin
4
x 5
+ cosx = 2 ........(ii)
Now equation (ii) will be true if sin
4
x 5
= 1 and cosx = 1
4
x 5
= 2nt +
2
t
, n e I and x = 2mt, m e I
x =
5
) 2 n 8 ( t +
, n e I ........(iii)
and x = 2mt, m e I ........(iv)
Now to find general solution of equation (i)
5
) 2 n 8 ( t +
= 2mt 8n + 2 = 10m
n =
4
1 m 5
if m = 1 then n = 1
if m = 5 then n = 6
......... ......... .........
......... ......... .........
if m = 4p 3, p e I then n = 5p 4, p e I
general solution of given equation can be obtained by substituting either m = 4p 3 in
equation (iv) or n = 5p 4 in equation (iii)
MATHS
"manishkumarphysics.in"
9
general solution of equation (i) is (8p 6)t, p e I
Self Practice Problems :
(17) Solve sin3x + cos2x = 2
(18) Solve 3 x cos x 5 sin 3
2
= 1 sinx
Answers : (17) (4p 3)
2
t
, p e I (18) 2mt +
2
t
, m e I
MATHS
"manishkumarphysics.in"
10
IMPORTANT POINTS :
1. Many trigonometrical equations can be solved by different methods. The formof solution obtained in different
methods may be different. From these different forms of solutions, the students should not think that the
answer obtained by one method are wrong and those obtained by another method are correct. The solutions
obtained by different methods may be shown to be equivalent by some supplementary transformations.
To test the equivalence of two solutions obtained from two methods, the simplest way is to put values of
n = .......2, 1, 0, 1, 2, 3....... etc. and then to find the angles in [0, 2t]. If all the angles in both solutions are
same, the solutions are equivalent.
2. While manipulating the trigonometrical equation, avoid the danger of losing roots. Generally, some roots are
lost by cancelling a common factor from the two sides of an equation. For example, suppose we have the
equation tanx = 2 sinx. Here by dividing both sides by sinx, we get cosx =
2
1
. This is not equivalent to the
original equation. Here the roots obtained by sinx = 0, are lost. Thus in place of dividing an equation by a
common factor, the students are advised to take this factor out as a common factor from all terms of the
equation.
3. While equating one of the factors to zero, take care of the other factor that it should not become infinite. For
example, if we have the equation sinx = 0, which can be written as cos x tan x = 0. Here we cannot put cosx
= 0, since for cos x = 0, tanx = sinx/ cosx is infinite.
4. Avoid squaring : When we square both sides of an equation, some extraneous roots appear. Hence it is
necessary to check all the solutions found by substituting them in the given equation and omit the solutions
not satisfying the given equation.
For example : Consider the equation,
sin u + cos u = 1 .....(1)
Squaring we get
1 + sin 2u = 1 or sin 2u = 0 .....(2)
i.e. 2u = nt or u = nt/2,
This gives u = 0,
2
t
, t,
2
3t
, ......
Verification shows that t and
2
3t
do not satisfy the equation as sin t + cost = 1, = 1
and sin
2
3t
+ cos
2
3t
= 1, = 1.
The reason for this is simple.
The equation (2) is not equivalent to (1) and (2) contains two equations : sin u + cos u = 1
and sinu + cos u = 1. Therefore we get extra solutions.
Thus if squaring is must, verify each of the solution.
5. Some necessary restrictions :
If the equation involves tanx, secx, take cosx = 0. If cot x or cosec x appear, take sinx = 0.
If log appear in the equation, i.e. log [f(u)] appear in the equation, use f(u) > 0 and base of log > 0, = 1.
Also note that )] ( f [ u is always positive, for example
u
2
sin
= sin u, not sin u .
6. Verification : Student are advice to check whether all the roots obtained by them satisfy the equation and lie
in the domain of the variable of the given equation.